A case of granulomatosis of polyangiitis presenting with COVID-19 infection: False-positivity or co-existence? - KAYA, MİTHAT; GÖKCE, İBRAHİM; ALPAY, HARİKA (My University, 2023)
Coronavirus disease 2019 (COVID-19) was declared a global pandemic and a public health emergency worldwide in March 2020. COVID-19 presents with non-specific symptoms of the upper airway and pulmonary system, which can overlap with other diseases involving the respiratory system as granulomatosis with polyangiitis (GPA). Both diseases have high morbidity and mortality rates and it is important to promptly differentiate and treat them. Real-time reverse transcriptase polymerase chain reaction (RT-PCR) is currently the recommended method for diagnosing COVID-19. Antibody-based tests are used to diagnose both pat and current COVID-19 infections. We present a previously healthy thirteen-year-old girl who was admitted with upper airway symptoms and pulmonary involvement, and progressed to acute kidney failure. Laboratory findings showed leukocytosis, anemia, elevated kidney function tests and 2+ proteinuria. Computed tomography (CT) of the lungs showed multiple nodules, cavities, and ground-glass opacities (GGOs). We performed RT-PCR tests for COVID-19 for three times. Results were all negative, but the COVID-19 immunoglobulin (Ig)M test sent simultaneously was positive. Based on the cytoplasmic antineutrophilic cytoplasmic antibody (c-ANCA) positivity, upper airway, pulmonary, and renal involvement, she was diagnosed as GPA. This report highlights that COVID-19 antibody tests can be false-positive in patients with autoimmune diseases including GPA.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; COVID-19; False-positive antibody test; Granulomatosis with polyangiitis